2016
DOI: 10.1177/0268580916662385
|View full text |Cite
|
Sign up to set email alerts
|

Do European citizens support the idea of a European welfare state? Evidence from a comparative survey conducted in three EU member states

Abstract: Some scholars have argued that the only way to resolve the Euro crisis would be to further deepen the integration process by institutionalising a European welfare state. This article examines whether a Europeanised welfare system would be supported by citizens of three member states of the EU. The authors argue that the legitimacy of a harmonisation of national welfare regimes would be established if a majority of citizens supported a Europeanised social policy. Using survey data from Germany, Poland and Spain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 41 publications
2
44
1
Order By: Relevance
“…Existing research has repeatedly shown that European identity is an important correlate of support for European social policy (Bechtel et al, ; Gerhards et al, ; Kuhn et al, ). While these studies have explored support for European social policy‐making in general, this article emphasizes the multidimensional nature of social policy (Gallego and Marx, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research has repeatedly shown that European identity is an important correlate of support for European social policy (Bechtel et al, ; Gerhards et al, ; Kuhn et al, ). While these studies have explored support for European social policy‐making in general, this article emphasizes the multidimensional nature of social policy (Gallego and Marx, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Gerhards et al . () show that European identity is also linked to support for European‐level welfare states. Similarly, Bechtel et al .…”
Section: Collective Identities and Support For European Social Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this reasoning, we can expect that citizens with lower socio-economic status are especially concerned about the EU's impact on social security, because their life chances are determined to a larger extent by national welfare provisions than those of higher socioeconomic status groups (Gerhards et al, 2016). In particular to welfare beneficiaries, European integration may represent a threat to social security as it might change the status quo of redistributive mechanisms (Beaudonnet, 2015).…”
Section: Individual-level Explanations: Utilitarian Interest and Ideomentioning
confidence: 99%
“…In addition, citizens in more-advanced welfare states evaluate the EU's impact on social security more negatively and are less willing to transfer social competences to the European level (Gerhards et al, 2016;Mau, 2005;Ray, 2004).…”
Section: Explaining Cross-national Differencesmentioning
confidence: 99%